Permasalahan Sempadan dan Tuntutan Wilayah: Kajian Latar Belakang Hubungan dan Sejarah Awal Hulu Perak-Reman Sebelum 1882: Border Issues and Territorial Claims: A Study on the Background of Early History and Relationships Between Hulu Perak and Reman Prior to 1882 - Rasidi, Shuwaibah; Zulkanain Abdul Rahman, (SEJARAH: Journal of the Department of History, 2023)
The history of Hulu Perak and Reman has been largely overlooked in local historical writings and studies, including those related to boundary demarcation. Most studies on the northern Malay States (NMS) border focus on discussions of British-Siamese relations without delving into the conflicts between these two regions. This paper aims to highlight this issue by examining the background of the territorial disputes between Perak and Reman before 1882. Qualitative research methods based on historical analysis and document analysis were used in this study. Thematic and descriptive approaches were employed in the analysis, which involved primary sources such as British records on microfilm and official files such as the Foreign Office (FO) and Colonial Office (CO) records, as well as secondary sources such as journals, books, newspapers, and online sources. The study of border issues between Hulu Perak and Reman before 1882 is significant from a historical and geopolitical perspective. It provides a clear understanding of the border conflict that influenced the political relations between these two regions. This study also contributes to future research on territorial boundaries in Malaysia. Received: 15 April 2023 Reviewed: 21 Jun 2023 Accepted: 30 September 2023